DEVELOPING OF MATHEMATICS LEARNING MULTIMEDIA BASED ON ICT IN STATISTICS MATERIAL - Rahma Siska Utari; Nike Astiswijaya (Jurnal Pedagogi Matematika, 2023)
This study aimed to develop valid and practical mathematics learning multimedia in statistics material in junior high school based on ICT. The mathematics learning multimedia developed in this research were learning videos, virtual classes, and learning evaluations. Multimedia learning mathematics was developed using various applications/software, like Google classroom, Google forms, PowerPoint presentation slides, FastStone capture, Kinemaster, and then the learning video uploaded on Youtube. This research was conducted using the design research method and development study type. The stages of this research were the preliminary and formative evaluation stages, which consist of the expert review, one-to-one, small group, and field test stages. The subjects of this study were 40 students of class VIII at SMPN 17 Palembang. Data were collected by observation, interviews, questionnaires, tests, and walkthrough. The multimedia learning mathematics developed was declared valid and practical. Validity was seen from result of revising products based on experts’ assignments at the expert review stage in terms of context, construct, and language. Practicality was seen during the one-to-one and small group stages, where the multimedia developed was easy for students to use.